Backcountry Ghosts : California Homesteaders and the Making of a Dubious Dream - Sides, Josh, 1972- (Book collections on Project MUSE., 2021)
"Josh Sides tells the remarkable stories of homesteaders in California, both those who succeeded and those who did not"--